Implementation Differentiated Learning to Improve Student Learning Outcomes CNC Machine Subjects Class XI TPM1 SMK Negeri 3Tanjungpinang - Fitrinaldi, Fitrinaldi; Suharyanto, Suharyanto; Rachmi, Rachmi; Nevrita, Nevrita; Kumalasari, Tetty; Irawan, Dody (SHS web of conferences, 2024)
This research aims to improve student learning outcomes in the CNC Machine subject in class XI TPM1 SMK Negeri 3 Tanjungpinang through the application differentiated learning methods. Initial observations showed gaps in students' understanding, where some experienced difficulties, while others felt less challenged. The differentiated learning method is applied by dividing students into groups according to their abilities and providing material appropriate to their respective levels understanding. This research uses the Classroom Action Research model which is carried out in two cycles. The research results show that there are differences in the achievement the Minimum Completeness Criteria (MCC) between student groups. Groups A and B consisted of 3 and 5 students who reached the MCC, while 60% students ingroup C succeeded in reaching the MCC, with the remaining 40% not yet adequate. The addition visual and interactive material in the second cycle had a significant impact on the understanding low group students. This method has proven effective in improving overall student learning outcomes.